The Influence of Perceived Ease of Use and Promotion on Interest in Using OVO E-Wallet in Surabaya City - Zayyan Hisyam Pradana; Siti Aminah (Indonesian Journal of Business Analytics, 2023)
The purpose of this study is to analyze and identify the influence of perception about ease of use and the influence of promotion on the interest of the people of Surabaya to use OVO e-wallet. This research is quantitative by using questionnaires as a data collection tool. The number of respondents involved in this study was 110 people. The questionnaire is created through Google Form for ease of dissemination. The sampling technique used is purposive sampling where respondents are determined selectively based on certain criteria according to the research objectives. The respondents involved in this study are residents of Surabaya City who live in Surabaya and understand and know about OVO e-wallet. The analysis technique used in this study uses SmartPLS with validity tests, reliability tests and hypothesis tests. Research shows that perceived ease of use and promotion have a positive and significant effect on interest in using. In other words, the higher the perception of ease of use and promotion, the higher the interest in using.